Absent Plasma Second Phase Platelet Aggregation Factor in a Patient with Hageman Trait - Okonkwo, P; Post, R; Sise, H (Thrombosis and Haemostasis, 1970)
A case is described of a patient with factor XII deficiency in whom the second phase of platelet aggregation was missing after addition of ADP to platelet rich plasma. There was very little aggregation on addition of epinephrine, collagen or thrombin. Clot retraction was absent, but all other platelet functions were normal and there was a very minor bleeding tendency. The defect was corrected by normal platelet poor plasma and was found to be due to a missing cofactor of platelet aggregation normally found in fraction 1–0. The defect could be distinguished from that seen in subjects ingesting aspirin as well as from the defect seen in patients with a long bleeding time, defective platelet aggregation with ADP, epinephrine and collagen at low concentrations, no correction by addition of normal platelet poor plasma, and a history of mild bleeding disorder. It is thought that this defect may exist in otherwise normal individuals and that attention in this case was called to it by the presence of the deficiency of factor XII. It could be conclusively shown that factor XII is not necessary for normal platelet aggregation.